A METHOD FOR ASSESSING ENERGY EFFICIENCY OF LIGHT-DUTY VEHICLES TAKING INTO ACCOUNT CHANGES IN THEIR DESIGN PARAMETERS - Halona, I. I.; Pitsyk, M. H.; Husiev, О. V.; Shapenko, Ye. M.; Sayliak, L. V. (Systems and Technologies, 2023)
The present stage of development of the world market of vehicles, in particular, light-duty vehicles (LDVs) is marked by an increasing variety of types and designs. Therefore, while validating or renewing fleet vehicle of an enterprise, carriers are faced with the choice of cars setting conditions they can assess using existing fragmentary and cost-effective approaches. However, the latter ones do not meet the concepts of saving energy and resources. Therefore, the task of choosing an efficient car is complex requiring a science-based formation of demands and their satisfaction. Existing approaches to the selection and validation of LDVs are simplified and imperfect in terms of transport technology. They do not take into account a) resource and technical properties of LDVs as a means of transport; b) main design and technical characteristics of LDVs; c) parameters of its operation (running surface, traffic density, length of the driving cycle, etc.). This article considers a method for assessing energy efficiency of light-duty vehicles, which is based on the scheme of the vehicle operation as a dynamic tool. To develop this method, the provisions of the energy and resource efficiency theory of a car have been used, namely the calculation schemes of transport operations based on models of reference prototypes and test operations. These models are able to ensure the reasonable use of the vehicle fleet with design novelty under the given operating conditions. In order to analyse changes in the parameters of new vehicles and improve the parameters of transport technology, a universal design of a light-duty vehicle of a generic type has been developed and considered. This structural pattern covers all options of the vehicle’s design basis. New options for the vehicle design are created by changing the number of design modules and their parameters. The method proposed for consideration ensures the technical and technological properties of light-duty vehicles in accordance with the concept of energy and resource conservation in the transport system. The paper develops methods for comprehensive improvement of transport energy efficiency and formation of requirements for transportation projects of LDVs taking into account technical and technological factors within their life cycle.